“Brief report: Investigating the relationship between PTSD symptoms and emotional intelligence among adolescent refugees from the Middle East” - Siti Raudzah, Ghazali (ASEAN federation of Psychiatry and Mental Health, 2014)
Objective: The objective of this study was to establish the relationship between symptoms of PTSD and various score of emotional intelligence scales. Methods: This study was a crosssectional research design. Participants were recruited from the local community health center in Dearborn, Michigan. Child Posttraumatic Stress Reaction Index (CPTS-RI) measured the presence of PTSD symptoms and the Adolescents Multifactor Emotional Intelligence Scale (AMEIS) measured emotional intelligence. Results: Findings suggest an inverse relationship between PTSD severity and emotional intelligence. The PTSD score was negatively correlated with all AMEIS subscales. Two significant negative correlations were found in the tasks of using emotion and understanding emotion. Conclusion: Findings suggest that individuals with severe PTSD symptoms appear to lack the abilities to understand and use emotions. It was expected that the findings will be useful in identifying factors that may decrease or contribute to decreasing the severity of PTSD symptoms of these children. Implications of the findings were discussed, and recommendations for future research were presented.